2002
DOI: 10.1016/s0014-5793(02)03311-2
|View full text |Cite
|
Sign up to set email alerts
|

High‐affinity urokinase‐derived cyclic peptides inhibiting urokinase/urokinase receptor‐interaction: effects on tumor growth and spread

Abstract: Urokinase-type plasminogen activator (uPA) binds with high a⁄nity to its speci¢c cell surface receptor (uPAR) (CD87) via a well-de¢ned sequence within the N-terminal region of uPA (uPA 19À31 . These peptides display an only ¢ve to 10-fold lower a⁄nity to uPAR as compared to the naturally occurring uPAR-ligand uPA. In this study, WX-360 and WX-360-Nle were tested in nude mice for their potency to inhibit tumor growth and intraperitoneal spread of lacZtagged human ovarian cancer cells. Intraperitoneal administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 25 publications
(48 reference statements)
0
32
0
1
Order By: Relevance
“…Our model raises the major concern that some small binding antagonists may in fact possess undesirable agonist effects on uPAR-mediated adhesion and migration on vitronectin-rich matrices. This ambiguity of action is illustrated by the inductive effects we observe for AE234, which actually was considered a potential lead compound for pharmaceutical intervention of uPA binding (42,46). Similar concerns are, however, less relevant for compounds belonging to the AE105-derived class of inhibitors.…”
Section: Resultsmentioning
confidence: 93%
“…Our model raises the major concern that some small binding antagonists may in fact possess undesirable agonist effects on uPAR-mediated adhesion and migration on vitronectin-rich matrices. This ambiguity of action is illustrated by the inductive effects we observe for AE234, which actually was considered a potential lead compound for pharmaceutical intervention of uPA binding (42,46). Similar concerns are, however, less relevant for compounds belonging to the AE105-derived class of inhibitors.…”
Section: Resultsmentioning
confidence: 93%
“…Synthetic cysteine proteinase inhibitors, selective for cathepsin B, have been shown to significantly reduce the invasiveness of MCF10AT cells (Bervar et al, 2003). Several studies using selective inhibitors of uPA or small, synthetic cyclic, competitive uPA antagonists derived from the binding sites of uPAR resulted in highly significant reduction of tumor burden (Evans et al, 1998;Sato et al, 2002). Very recent studies have also shown that fusion of diphtherotoxin with the ATF-uPA caused a statistically significant regression of glial tumors and was highly potent and selective at killing uPAR expressing glioblastoma cell lines (Vallera et al, 2002).…”
Section: Cathepsin B and Upar Sirna Suppresses Intracranial Tumor Growthmentioning
confidence: 99%
“…10B,C) (Burgle et al, 1997;Magdolen et al, 2001). These cyclic peptides were able to compete with Sato et al, 2002). Down regulation of uPAR expression has also been achieved in pre-clinical models using anti-sense and gene therapy approaches leading to increased tumor dormancy, suppression of tumor growth and metastasis development (Kook et al, 1994;Li et al, 1998 and1999;Aguirre Ghiso et al, 1999, Mohan et al, 1999.…”
Section: Proteolytic Systems As Therapeutic Targetmentioning
confidence: 99%